Pengaruh Latihan Buerger Allen Exercise terhadap Perfusi Perifer Pasien Diabetes Melitus Tipe II - Suratun, Suratun; Dani, Wulan Rahma; Nabila, Ananda Prisa Putri; Pandega, Ananda Rizti (Universitas Malahayati, 2025)
ABSTRACT Peripheral tissue perfusion disorders occur due to decreased blood circulation to the periphery so that blood cannot flow normally throughout the body. Ineffective peripheral tissue perfusion in patients with diabetes mellitus is a common complication and is a nursing problem that must be anddressed quickly so that more severe complications do not occur, blood circulation that is not smooth will cause emergencies in patients with diabetes mellitus. Decreased circulation can be characterized by frequent tingling, muscle cramps, stiffness and cold hands, dry and cracked skin and slow healing wounds. Narrowing of the arteries or periphery can be measured through non-invasive examinations, one of which is the Ankle Brachial Index (ABI) examination which functions to detect clinical signs and symtoms of decreased peripheral perfusion that can cause diabetic angiopathy and neuropathy. Actions that can be recommended for patients with peripheral perfusion disorders include physical exercise to improve blood circulation with Buerger Allen Exercise. The purpose of this study was to determine the effect of Buerger Allen Exercise on peripheral perfution in patients with Type II DM. method: quantitative research design with quasi-experimental design one group pre and post test on a sample of 24 respondents at the Muhammadiyah Hospital Palembang. Data analysis using dependent t-test. The results of the study showed the effect of Buerger Allen Exercise on peripheral perfusion of Type II DM patients with a p-value 0.004. Keywords: Buerger Allen Exercise, Peripheral Perfusion, Type II DM ABSTRAK Gangguan perfusi perifer jaringan terjadi dikarenakan penurunan sirkulasi darah ke perifer sehingga darah tidak dapat mengalir secara normal keseluruh tubuh. Ketidakefektifan perfusi jaringan perifer pada penderita diabetes mellitus merupakan komplikasi yang sering terjadi dan merupakan masalah keperawatan yang harus diatasi dengan cepat agar tidak terjadi komplikasi yang lebih berat, sirkulasi darah yang tidak lancer akan menyebabkan kegawadaruratan pada pasien diabetes mellitus. Penurunan sirkulasi dapat ditandai dengan sering kesemutan, kram otot, kaku dan tangan terasa dingin, kulit kering dan pecah-pecah serta luka lambat sembuh. Penyempitan arteri atau perifer dapat diukur melalui pemeriksaan non invasive salah satunya adalah dengan pemeriksaan Ankle Brachial Index (ABI) yang berfungsi untuk mendeteksi tanda dan gejala klinik dari penurunan perfusi perifer yang dapat mengakibatkan angiopati dan neuropati diabetic. Tindakan yang dapat dianjurkan pada pasien diabetes mellitus dengan gangguan perfusi perifer salah satunya adalah latihan fisik untuk meningkatkan sirkulasi darah dengan latihan Buerger Allen Exercise. Tujuandari penelitian ini untuk mengetahui pengaruh latihan buerger allen exercise terhadap perfusi perifer pasien DM Tipe II. Desain penelitian kuantitatif dengan rancangan quasi eksperimen one group pre dan post tes pada sampel yang berjumlah 24 responden di Rumah Sakit Muhammadiyah Palembang. Analisis data menggunakan uji dependen t-tes. Hasil penelitian ada pengaruh latihan Buerger Allen Exercise terhapa perfusi perifer pasien DM Tipe II dengan p-Value 0,004. Kata Kunci: Buerger Allen Exercise, Perfusi Perifer, DM Tipe II.